ПРИНЦИПЫ ПРАВОВОГО РЕГУЛИРОВАНИЯ ОТНОШЕНИЙ В ОБЛАСТИ ИСПОЛЬЗОВАНИЯ И ОХРАНЫ ЗЕМЕЛЬ ГОРОДОВ И ИХ СОДЕРЖАНИЕ (Journal of actual problems of jurisprudence, 2019)
In this article the author upon the principles legal regulation of use and protection of land the city and their contents